'Everything Looks Better from the Seat of a Bike': a qualitative exploration of the San José Bike Party. Issue 2 (3rd April 2018) - Johnson, Jay; Masucci, Matthew; Signer-Kroeker, Mary Anne
ABSTRACT: The San José Bike Party (SJBP) originated in 2004–2005 as a diverse collection of cyclists joining together for group rides in and around San José, California. By 2007, a core group of organizers intentionally avoided the overt political overtones of the often-controversial Critical Mass ride for a more benign and 'fun' gathering. The ride, which currently attracts between 1, 000 and 4, 000 cyclists, is often organized around specific themes, such as 'World Cup' and 'Superheroes.' Upon closer examination, however, there seems to be contradictory experiential narratives that do not necessarily align with the organization's mission statement, Building community through bicycling. The purpose of this paper is to present results from a qualitative examination of the SJBP. Through analysis and thematization of a series of semi-structured interviews, focus group data, and field observations, the complexities of the often contested and negotiated meanings assigned to the event by SJBP participants are presented.